As mudanças da cadeia produtiva têxtil em Valença-RJ: das indústrias do setor de tecidos para o APL do setor de Confecções - Coutinho, Gisela Aguiar Soares (2007)
This study shows how the Industrial Cluster of garments in Valença, RJ ¿ comprised of micro and small enterprises ¿ contributes to overcome the problems left by the declining period of the textile industry. At first, the city took advantage of its talent for textile work and turned to the clothing sector, which now relies on garment factories, subcontractors, cooperatives and laundries in order to create jobs. There is institutional support, but the analysis of the situation identified the need for higher involvement of cluster players, as well as a higher interaction among them to help their own development. In regard to public and private institutions, there is room for steps to guide informal companies that find it difficult to afford labor, financial, and environmental costs towards formalization, the offer of management and labor skill programs, as well as entrepreneurs¿ awareness about the acquisition of modern-technology machinery. It is important to encourage higher participation of Valença firms in the national fashion events, since this draws attention to the name of the city, discloses the work that is carried out there, and attracts new businesses. The entry of Valença companies in the fashion arena of the southern region of Rio de Janeiro state is beneficial, especially to make them better prepared for the Fashion Rio/Fashion Business event. Informality as a way out of the unemployment problem is a growing trend in Valença, as well as in most of Brazilian cities. In this sense, the entrepreneurs need to find favorable steps to make them feel motivated to formalize their businesses.